HUBUNGAN ANTARA MEROKOK DENGAN KASUS TB DAN UPAYA PENGOBATAN DI WILAYAH PUSKESMAS CIBEUREUM KOTA TASIKMALAYA - Wawan Rismawan; Yayah Syfariah (LPPM Universitas Bakti Tunas Husada, 2015)
Background: Until recently, tuberculosis (TB) among children in Indonesia is still becoming a health problem. Early detection and treatment compliance are keys to the success of controlling program of TB. Fact says that only 29% of community visit health centers after the symptoms lead to TB. Community perception toward the danger of disease plays an important role in health seeking behavior. Objective: To increase community perception about smoking and tuberculosis in Tasikmalaya District and to increase of new case detection coverage. Method: This was a quantitative and qualitative study with a cross sectional study design. Samples were 142 people. Tasikmalaya District. Data were collected through closed questionnaire and in-depth interview on four informants. Quantitative data were then analyzed with chi-square test and binomial regression. Meanwhile, qualitative data were analyzed using content analysis. Results: Bivariable analysis showed that the perception about TB was significantly related to health seeking behavior. Parents who had a good perception about TB had an opportunity 1.3 times greater to health seeking behavior than the group who had a poor perception about TB. High education was significantly related to health seeking behavior (RP=1.3; p=0.005 CI 95%=1,07-1,57, respectively) but age, knowledge, information source, family income and motivation were not significant. Meanwhile, results of multivariable analysis showed that education did not change the opportunity for health seeking behavior to health providers. Finally, results of qualitative analysis showed that TB had a greater severity than vleck. Conclusion: Smoking had not significant relationship with TB but Perception about TB and education had a significant relationship with health seeking behavior.